Web softwares and applications [ - Reeve, Brielle (New York : Learning Press, 2014)
This is an integrated handbook of web softwares and applications
1. Web browser -- 2. Blog software -- 3. Web application -- 4. Template engine -- 5. Web crawler -- 6. Web search engine -- 7. Web server -- 8. Content-control software -- 9. Internet information services -- 10. Search engine optimization
Keywords: Web services; World Wide Web